Common factors in altered states: understanding psychedelic therapy through the lens of Grawe’s general change mechanisms$dpsychological review - Wolff, Max; Rutrecht, Hans; Mertens, Lea Julia; Meijer, Andy A.; Beck, Jessica; Pérez, Sergio; Gründer, Gerhard; Dziobek, Isabel; Jungaberle, Henrik (Psychological review, 2025)
Psychedelic therapy is commonly understood as a form of psychotherapy. However, despite promising results from clinical trials, scientific progress has been hindered by a lack of theoretical integration between the fields of psychedelic and psychotherapy research. This article seeks to bridge this divide by outlining a transtheoretical understanding of psychedelic-occasioned psychological change based on Klaus Grawe’s model of general change mechanisms—an empirically grounded framework of psychotherapeutic “common factors” that emphasizes therapeutic experiences and change processes. Drawing on extensive evidence from psychedelic research, we argue that the efficacy of psychedelic therapy is ultimately mediated by the same five general change mechanisms that underlie all effective psychotherapies: (1) resource activation, (2) therapeutic relationship, (3) problem actuation, (4) clarification, and (5) mastery. Implications for clinical practice, training, and future research are discussed. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 09.12.2025